MRI of the knee in asymptomatic adolescent swimmers: a controlled study. Issue 4 (3rd April 2011) - Soder, Ricardo Bernardi; Mizerkowski, Mariana Damian; Petkowicz, Rose; Baldisserotto, Matteo
Abstract : Background: Swimming is a widespread sporting activity generally regarded as an ideal form of exercise, which has little or no impact on the knees. However, overuse or repetitive microtrauma injuries may often affect the knee joint of young competitive swimmers. These early lesions are frequently asymptomatic for a considerable period of time before causing discomfort or joint pain. Purpose: The aim of the present study is to use MRI to evaluate the knee joints of asymptomatic young elite swimmers and to compare them with age- and sex-matched controls who do not practice any impact sports regularly. Study design: Cross-sectional case–control study. Material and methods: The authors performed a cross-sectional controlled study to evaluate 54 knees of 27 asymptomatic male adolescents aged 14–15 years, paired by age and weight. Participants were divided in two groups: 13 elite swimmers and 14 control adolescents. The authors performed all the exams using a 0.35-T open-field MRI unit and evaluated by two experienced radiologists blinded to study groups. The images were evaluated to detect the presence or absence of abnormalities. Results: One or more imaging abnormalities were detected in 18 knees in the group of swimmers (69.2%; p=0.013). The most prevalent findings in the athletes were infrapatellar fat pad edema (53.8%; p=0.049), followed by bone marrow edema (26.9%; p=0.022), edema of prefemoral fat pad (19%; p=0.022) and joint effusion (15.3%; p=0.047). Conclusion: Significantly more MRI abnormalities were found in the knee joints of asymptomatic adolescent elite swimmers. This high prevalence of positive imaging findings in swimmers may correspond to benign changes or preclinical lesions, which should be evaluated in a follow-up study.